'At each remove the similarity fades a bit more': queer politics and experimental prose in two generations of New Narrative. Issue 8 (3rd August 2021) - Hester, Diarmuid
ABSTRACT: In the absence of a wide-ranging literary history that would take into account both the initial impetus for New Narrative's creation and the changes wrought as a younger generation came on the scene, New Narrative can seem rather monolithic as a movement. A newcomer to New Narrative may be left with the false impression that the ideas first proposed by Bruce Boone and Robert Glück remained relatively static over time. This essay attempts to expand the historical frame previously applied to New Narrative. Thinking genealogically about the movement and examining different writers' approaches to politics especially, it traces the shift from first to second generation, building on previous attempts to narrate New Narrative's complex story.